Serat Kalatidha Analysis: Integrating Educational Character Through Local Cultural Resources of Javanese Culture - Zuminati Rahayu (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
One of Local wisdom in the form of character noble is tembang macapat. Tembang macapat as one the Javanese literary works will be piwulang. Local wisdom is developed among the community through oral tradition in the form of habits singing tembang macapat either individually or collectively. One of the famous tembang macapat is Serat Kalatidha written by Ranggawarsita fromSurakarta's royal family. Serat Kalatidha contains the moral education and character values that are useful for life. Moral values in Javanese cases if examined and observed contents are still relevant to today's society life. So it can be used as a role model and a source of moral values for Indonesian. In the current era of the globalization, there is a tendency of people to accept outside cultures directly, this is not necessarily good and useful. For that can be anticipated by keeping take care values of local cultural wisdom. The moral values that contained in Serat Kalatidha, is a legacy inheritance believed by society in the past, which can be used as character formation.